Transição energética e engajamento público em Moçambique - Pereira, Crescêncio; Gonçalves, Euclides; Forquilha, Salvador (Desafios para Moçambique 2022, 2022)
Este estudo mostrou que, para serem analiticamente mais produtivos, os conceitos de circulação global, como o de transição energética, precisam ser adaptados para dar conta de realidades específicas num mundo que, historicamente, tem produzido relações desiguais. No caso de Moçambique, a estratégia para a transição energética passa pela exploração do gás natural, mas esta abordagem tem como limitação as características da indústria extractiva que produz poucas oportunidades de desenvolvimento ao nível local e tem o potencial de produzir impactos ambientais e sociais nefastos. Pressupostos de noções como engajamento público ou participação pública devem também ter em conta os contextos onde são introduzidas, de forma inseri-las nas dinâmicas de poder local e capitalizá-las com as experiências positivas existentes. No caso de Moçambique, foi demonstrado que qualquer entendimento ou estratégia para um engajamento público para uma transição energética deve considerar os níveis de abertura do espaço cívico, das capacidades dos cidadãos e das organizações da sociedade civil, e de pobreza energética nas regiões de extracção de recursos naturais. Em regiões como o Norte de Moçambique, onde níveis baixos de cobertura da rede de energia eléctrica se combinam com múltiplas formas de pobreza, os cidadãos colocam os problemas associados à transição energética em segundo plano em favor das necessidades relativas ao desenvolvimento local. Este estudo sobre transição energética e engajamento público em Moçambique mostrou os desafios que os intervenientes do subsector do petróleo e gás têm para mobilizar e expandir o espaço de debate público sobre formas de avançar no processo de transição energética em Moçambique. Da experiência de engajamento público existente, identificámos os três principais espaços de interacção ao nível internacional, nacional/central e ao nível local. Estes espaços de engajamento seguem dinâmicas mais ou menos autónomas e com poucas interligações. Experiências de engajamento público de Moçambique e outras partes do mundo mostram que as estratégias com maior nível de sucesso reconhecem a necessidade de articulação entre o Governo, as organizações da sociedade civil e a responsabilidade social das empresas para garantir o envolvimento das comunidades, além das convencionais consultas que são realizadas em exercícios para a mitigação dos impactos dos projectos.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; citizenship & participation / cidadania e participação; natural resources / recursos naturais; politics / política

Could Mozambique become a hydrogen hub? - Hanlon, Joseph (Mozambique News Reports & Clippings, 2021)
The proposal for the Mphanda Nkuwa dam 60 km downstream from Cahora Bassa, and using the same water to generate more electricity, is back on the table. The dam has been proposed since the colonial era, but there has never been a market for the electricity. Producing hydrogen would be the perfect market. In this special issue, we look at Mphanda Kkuwa and the potential for hydrogen.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; GP - Tete; L - english / inglês; infrastructure - energy / infrastrutura - energia; natural resources / recursos naturais

Vale moves to exit coal business - Argus Media (2021)
In its first step to exit the coal business, Brazilian mining firm Vale will acquire all stakes held by Japanese trading house Mitsui in the Moatize coal mine and Nacala corridor coal infrastructure in Mozambique.
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; extractive industries / indústrias extractivas; natural resources / recursos naturais

Mozambique: Syrah Resources resumes graphite mining ahead of schedule after year's stoppage (Mozambique, 2021)
Australian mining company Syrah Resources has resumed production of graphite ahead of schedule at its Balama mine in Cabo Delgado, northern Mozambique, it said in a statement to shareholders on Tuesday. The plant's activities were halted in late March last year following the country's implementat
Keywords: #Reporting & Media / Reportagem & Mídia; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; natural resources - mining / recursos naturais - mineração; natural resources / recursos naturais; private sector / setor privado

Altona Rare Earths soars as it enters MoU to acquire rare earths project (Vox Markets, 2021)
Shares in Altona Rare Earths soared by over 60% today following the news that the group has entered into an MoU to acquire up to 70% in the Monte Muambe Rare Earths Project. Should it choose to proceed with the investment following a 90-day due diligence period, the project would represent its first venture into a carbonatite hosted REE asset.
Keywords: #Reporting & Media / Reportagem & Mídia; G - Mozambique / Moçambique; G - central / centro; GP - Tete; L - english / inglês; natural resources - mining / recursos naturais - mineração; natural resources / recursos naturais

Moma Titanium Minerals Mine, Mozambique - Mining Technology | Mining News and Views Updated Daily - Mining Technology (Mining-technology, 2021)
Moma, one of the world’s biggest titanium mineral deposits, is located 160km from the city of Nampula in Mozambique, Africa. It is owned and operated by Kenmare Resources. The mine contains the titanium minerals ilmenite, rutile and zircon, which are used as feedstock to produce titanium dioxide pigment. It started production of heavy mineral concentrate (HMC) containing these three minerals in April 2007. It produced 1,201,100t of HMC and shipped approximately 853,100t of finished products in 2020. Kenmare carried out an expansion at the mine ten years ago to fulfil the growing demand for titanium dioxide feedstock in the market. The expansion was aimed to increase the design capacity of the mine by 50% while increasing the mine’s reserve estimate and annual production of HMC. Construction work on the expansion began in December 2010 and the works were completed in December 2013. The expanded mine has a mine life of more than 100 years. The first shipment of concentrated mineral sands was dispatched from Mama in Q2 2019, following the commissioning of the product stream in Q4 2018. The Moma mine had more than 1,420 employees at the end of 2019.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; L - english / inglês; extractive industries / indústrias extractivas; natural resources - mining / recursos naturais - mineração; natural resources / recursos naturais

Relatório Independente da Iniciativa de Transparência na Indústria Extractiva - EITI (Extractive Industries Transparency Initiative (EITI), 2020)
Este é o nono relatório de reconciliação dos pagamentos efectuados pelas empresas que operam na indústria extractiva e os recebimentos do Estado. Foram reconciliadas 97% das receitas tributárias provenientes da indústria extractiva. As diferenças apuradas entre os pagamentos das empresas e os recebimentos do Estado correspondem a 0,17% dos montantes confirmados pelo Estado em 2019.
Keywords: *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; extractive industries / indústrias extractivas; natural resources / recursos naturais

Economia Política da Governação de Recursos Naturais em Nampula - Salimo, Padil (Akilizetho – ADS, 2020)
A Akilizetho-ADS elaborou um estudo denominado Economia Política da Governação dos Recursos Naturais, em Nampula. A pesquisa foi feita entre Dezembro de 2019 e Janeiro de 2020. A abordagem do estudo foi baseada numa análise de economia política e circunscrito apenas aos recursos minerais e hidrocarbonetos. O objectivo do estudo foi de compreender as relações entre governos, empresas extractivas, comunidades, sociedade civil e reflectir sobre as dinâmicas de governação da indústria extractiva e suas implicações sobre os direitos das comunidades afectadas.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; L - portuguese / português; natural resources / recursos naturais

The presource curse in Africa: Economic and political effects of anticipating natural resource revenues - Frynas, Jedrzej George; Buur, Lars (The Extractive Industries and Society, 2020)
The notion of the ‘resource curse’ suggests that large inflows of extractive industry revenues cause many adverse macro-economic and political effects. The resource curse literature focuses on the impact of actual inflows of extractive resource revenues. However, anticipation of future resource revenues can also lead to negative macro-economic and political effects even before resource extraction takes place, which points to the role of behavioral aspects of the ‘resource curse’. Using empirical evidence from three African countries, this article investigates to what extent the anticipation of future extractive revenues led to ‘presource curse’ effects. It finds that all three countries experienced negative effects as a result of anticipation of future extractive revenues, including economic growth volatility, higher levels of national debt, eroded governance and societal conflicts. Given the phenomenal increase in oil, gas and metal ore exploration across Africa, it is likely that many countries experience the negative effects of a presource curse without natural resource extraction or long before natural resources are actually extracted.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; extractive industries / indústrias extractivas; natural resources / recursos naturais

The politics of domestic gas: The Sasol natural gas deals in Mozambique - Salimo, Padil; Buur, Lars; Macuane, Jose Jaime (The Extractive Industries and Society, 2020)
This article explores the ways in which the ruling Frelimo elite in Mozambique engaged creatively with the opportunities and constraints created by Sasol's Pande and Temane natural gas project as they have evolved from the early 2000s until today. This is a period that has seen ruling-elite actors become involved in various projects related to the production of electricity from ‘domestic natural gas’. We argue that focusing on the initial gas investment and how it evolved over time makes it possible to understand the dynamics related to deal-making during the formative years when the Mozambican petroleum industry was reformed by separating its commercial and regulatory functions. More specifically we explore how access to revenues and rents related to natural gas projects have evolved. We point out that, although the Pande-Temane gas project has increased revenue generation, most of the gas was sold to the South African major, Sasol, for a very low amount of revenue during the first phase of the project. Revenues from the second phase, starting in 2012, did not increase dramatically, even though Mozambique acquired access to 50% of the gas from the extension of the pipeline and increased production. Instead, the increase in domestic gas allocated to the Mozambican market involved the allocation and distribution of gas to private companies at special prices, most of which were controlled by dominant ruling-elite factions under the Chissano and Guebuza governments. We argue that this has been the main mechanism for the transfer of rents from the public to the private domain.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; extractive industries / indústrias extractivas; natural resources - gas / recursos naturais - gás; natural resources / recursos naturais

Natural resources, institutions, and economic transformation in Mozambique - Macuane, Jose Jaime; Muianga, Carlos (2020)
In the light of Mozambique’s natural resources boom—especially its large-scale investments in mining, oil, and gas—this paper analyses the prospects for the extractive industries to contribute to economic transformation from an institutional perspective. To this purpose, we address the institutional dynamics of the resources sector and consider the underlying causes of the identified outcomes. The National Development Strategy, as the instrument presenting the vision for economic transformation and diversification, is discussed. The paper is based on a desk review—documental and bibliographic—and on primary data gathered by the authors as part of their research into the field of natural resources and the political economy of development. We conclude that, given Mozambique’s political patronage and clientelism, intra-ruling elite competition, limited productive base, weak state capacity, high level of poverty, and recurrent fiscal deficits, the prospects of the current resource boom leading to economic transformation, despite its considerable potential, are at best uncertain.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; economic development / desenvolvimento económico; institutions / instituições; natural resources - gas / recursos naturais - gás; natural resources - mining / recursos naturais - mineração; natural resources / recursos naturais

Recursos naturais, instituições e transformação económica em Moçambique - Macuane, Jose Jaime; Muianga, Carlos (2020)
Face ao boom de recursos naturais em Moçambique — em especial dos seus grandes investimentos em exploração mineira, petróleo e gás —, este documento analisa a perspectiva de as indústrias extractivas contribuírem para a transformação económica de um ponto de vista institucional. Para esse efeito, abordamos a dinâmica institucional do sector dos recursos e consideramos as causas subjacentes aos resultados identificados. É discutida a Estratégia Nacional de Desenvolvimento enquanto instrumento que apresenta a visão para a transformação e diversificação económica. O documento baseia-se numa revisão documental e bibliográfica e em dados primários recolhidos pelos autores no âmbito da sua investigação no campo dos recursos naturais e da economia política do desenvolvimento. Concluímos que, dado o patrocínio político e o clientelismo de Moçambique, a competição no interior da elite governante, a base produtiva limitada, a fraca capacidade do Estado, o elevado nível de pobreza e os défices fiscais recorrentes, as perspectivas de que o actual boom de recursos leve à transformação económica, apesar do seu considerável potencial, são, na melhor das hipóteses, incertas.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; economic development / desenvolvimento económico; institutions / instituições; natural resources - gas / recursos naturais - gás; natural resources - mining / recursos naturais - mineração; natural resources / recursos naturais

Extractive Industry Transparency Index 2019-2020 - Mapisse, Inocência; Mate, Rui; Cortez, Edson (Centro de Integridade Pública (CIP) / Public Integrity Centre, 2020)
The extractive industry, particularly the oil and gas sector, has proved promising in the Mozambican economy with potential to contribute to economic growth. It is expected that in the next 3 years the country will show growth in the order of two digits. However, in order to ensure the transmission of growth to economic development based on the exploitation of these resources, there are aspects that should not be ignored such as transparency in governance in the sector. This aspect is also recognized by the government of Mozambique through the Report on Transparency, Governance and Corruption published in July 2019, which emphasizes that the opacity in this sector can give rise to serious conflicts of interest and harm the perception of the population about the real benefits that this industry provides to the country. Although the country is part of the Extractive Industry Transparency Initiative (EITI), whose focus is on the reconciliation of payments made by companies and receipts reported by the Government in the extractive industry sector, there is a gap regarding detailed information on several aspects: tax, social, governmental and other equally relevant and that should be made available on a project-by-project basis.
Keywords: *tagged; G - Mozambique / Moçambique; L - english / inglês; extractive industries / indústrias extractivas; natural resources - gas / recursos naturais - gás; natural resources - mining / recursos naturais - mineração; natural resources / recursos naturais; transparency / transparência

Como Está Cabo Delgado? Webinar 2: Economia Política Dos Recursos Naturais - Observatório do Meio Rural (2020)
Com a entrada no novo milénio, e em virtude do aumento da procura de matérias primas nos mercados internacionais, intensifica-se um modelo de desenvolvimento assente na exploração de recursos naturais. Em Cabo Delgado emerge uma economia extractiva, fortemente dirigida para mercados externos e dependente da oscilação de preços nos mercados internacionais, que o país não tem condições de controlar. Grandes multinacionais envolvem-se numa acesa competição pelo acesso a recursos, em complexas alianças com elites nacionais, também elas em disputa entre si. Neste webinar pretende-se reflectir sobre as lógicas de acumulação aqui envolvidas, assim como o impacto que poderá ter para Moçambique em termos de receitas fiscais, e de desenvolvimento nacional.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; M - political economy analysis (PEA) / análise de economia política (AEP); extractive industries / indústrias extractivas; natural resources / recursos naturais

War in resource-rich northern Mozambique – six scenarios 2020.pdf - Santos, F. A. dos (Chr. Michelsen Institute, 2020)
Since the October 2017 attacks by alleged Islamist insurgents, commonly referred to as Ahlu Sunnah Wa-Jama and locally know as Al Shabab, on Mocimboa da Praia, it has not been entirely clear who the attackers were, what their strategic objectives are and on whose domestic and international support they rely. This paper, grounded in a historical understanding of conflict in northern Mozambique’s Cabo Delgado Province, seeks to identify possible stakeholders and scenarios in what we no longer see as an insurgency, but a war.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; Northern PEA; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; natural resources - gas / recursos naturais - gás; natural resources / recursos naturais

Mozambique - Invest in the Energy Sector of Mozambique - African Oil and Power (Africa Energy Series, 2020)
Since initial exploratory drilling in 2007 by U.S. operator Anadarko, Mozambique has uncovered vast natural gas volumes within its offshore basins, and now carries the potential to be the fourth largest natural gas exporter globally. With discoveries ranging from Anadarko’s initial 480 feet of gas found in Area 1 in 2010, to Eni’s discovery of 425 billion cubic meters one year later, the onus now lies on major operators including Royal Dutch Shell, Total, Eni and more to develop the requisite infrastructure to exploit the reserves, generate exports and bring revenue into the country. Potential inhibitors to the development of such resources include two ‘black swan’ events that have occurred since early-2020. In addition to the onset of COVID-19 in March – including a specific outbreak on Total’s Mozambique LNG development – the gas-rich Cabo Delgado province is facing a growing Islamist insurgency that began in the country in 2017. Nevertheless, the world-class nature of Mozambique’s gas assets has offset such inhibitors, and the country recently secured the largest foreign direct investment in Africa to date through its Mozambique LNG development. Gas monetization projects push forward on schedule, as the nation continues on its path to becoming a global energy giant.
Keywords: G - Mozambique / Moçambique; L - english / inglês; infrastructure - energy / infrastrutura - energia; natural resources / recursos naturais

Finanças Internacionais e Formação do Capitalismo Nacional em Moçambique - Castel-Branco, Carlos Nuno (Desafios para Moçambique 2020, 2020)
Este capítulo descreve e explica como e por que razão a economia moçambicana e as suas dinâmicas de expansão e de crise, as suas contradições e os seus paradoxos foram estruturados e articulados pela sua relação de dependência com o capital financeiro privado internacional, e as implicações desta relação para as características, as dinâmicas e as opções de acumulação privada de capital e de desenvolvimento da sociedade como um todo em Moçambique.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; natural resources / recursos naturais; private sector / setor privado

Additional Financing to the Agriculture and Natural Resources Landscapes Management Project (SUSTENTA) - World Bank (World Bank, 2019)
Proposed Development Objective(s) Parent The project development objective is to integrate rural households into sustainable agriculture and forest-based value chains in the Project area and, in the event of an Eligible Crisis or Emergency, to provide immediate and effective response to said Eligible Crisis or Emergency. Components Agriculture and Forest-Based Value Chain Development Securing Land Tenure Rights and Increasing Natural Resources Resilience Project Coordination and Management Contingency Emergency Response
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; development partners / parceiros de cooperação; governance / governação; land governance / gestão de terra; natural resources / recursos naturais

Sound of One Hand Clapping: Information Disclosure for Social and Political Action for Accountability in Extractive Governance in Mozambique - Awortwi, Nicholas; Nuvunga, Adriano (IDS, 2019)
Corruption through opaque public contracts costs Africa billions of dollars in revenue loss annually. Globally, initiatives to address this have centred on information disclosure (ID) but under what conditions does it work to promote accountability in the extractive sector that for a long time has seen its revenue management as being a major cause of conflict in Africa? Our study on this issue in Mozambique reveals intriguing findings, which suggest that protagonists of ID would need to recalibrate their strategies for promoting accountability. The study on ID in extractive governance in Mozambique has found 17 factors that connect to result in citizen and institutional inaction in demanding government accountability. The lessons from the study for policy and practice are that unless there is a link between ID and a government’s reputation, which scales up to the risk of a ruling government losing power, accountability is unlikely to occur when new information is disclosed.
Keywords: *tagged; G - Mozambique / Moçambique; L - english / inglês; accountability / responsabilização; citizenship & participation / cidadania e participação; corruption / corrupção; decentralization / descentralização; extractive industries / indústrias extractivas; natural resources / recursos naturais

Independent Report of the Extractive Industries Transparency Initiative - EITI (Extractive Industries Transparency Initiative (EITI), 2019)
This is the ninth report reconciling payments made by companies operating in the extractive industry and receipts from the State. 97% of tax revenues from the extractive industry were reconciled. The differences between the payments by the companies and the receipts from the State correspond to 0,17% of the amounts confirmed by the State in 2019
Keywords: *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; extractive industries / indústrias extractivas; natural resources / recursos naturais

Moçambique - recessão antes do boom: Reflexões sobre picos de investimento e novas fontes de gás - Roe, Alan (2018)
Este artigo surge na sequência de um artigo anterior onde se considerou em termos gerais muitas das questões que Moçambique enfrenta hoje em dia na gestão dos seus novos recursos extractivos. Em primeiro lugar descreve-se o pico de investimento já desencadeado pelas novas descobertas de gás em Moçambique. Depois apresenta-se em resumo alguma da literatura mais recente sobre os efeitos desses picos noutros países e contextos. De seguida analisam-se os principais aspectos dos resultados económicos decepcionantes testemunhados até 2018, e analisase selectivamente algumas das implicações destes resultados nas políticas futuras. O artigo conclui explorando a epidemiologia de um grande pico do investimento público — uma questão que tem relevância para o pico adicional que ainda é esperado. Ao seguir esta sequência de argumento, procura-se igualmente compreender melhor diversas questões fundamentais de política geral que surgem no contexto das grandes descobertas de novos recursos.
Keywords: *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; L - portuguese / português; extractive industries / indústrias extractivas; natural resources - gas / recursos naturais - gás; natural resources / recursos naturais

Mozambique - bust before boom: Reflections on investment surges and new gas - Roe, Alan R. (WIDER Working Paper Series, 2018)
This paper is a sequel to an earlier paper that looked in broad terms at many of the issues that Mozambique faces today in managing its new extractive resources. The paper first describes the investment surge that has already been prompted by new gas discoveries in Mozambique. It then summarizes some of the more recent literature that has examined the effects of such surges in other country contexts. It next examines the main aspects of the disappointing economic outcomes that have so far been seen through 2018, and selectively analyses some of the implications of these outcomes for future policy. The paper concludes by exploring the epidemiology of a large public investment surge—an issue that has relevance for the further surge that is still anticipated. In following this sequence of argument, the paper also throws light on a number of critical general policy questions that arise in the context of major new resource discovery.
Keywords: *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; extractive industries / indústrias extractivas; natural resources - gas / recursos naturais - gás; natural resources / recursos naturais; ⛔ No DOI found

What are the prospects for Mozambique to diversify its economy on the back of 'local content'? - Dietsche, Evelyn; Esteves, Ana Maria (WIDER Working Paper Series, 2018)
In recent years, Mozambique has made international headlines for the significant hydrocarbon deposits found offshore. These have increased the country's extractive resource endowments, in addition to its mining and onshore natural gas sector. It is expected that these industries will contribute to economic diversification and social development, not least by means of procuring locally produced goods and services and hiring Mozambicans. A key factor to achieve this is building domestic capital?in people, institutions, and infrastructure.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; extractive industries / indústrias extractivas; natural resources / recursos naturais; private sector - CSR (corporate social responsibility) / setor privado - RSC (responsabilidade social corporativa); ⛔ No DOI found

Islamic Insurgency in Cabo Delgado: Extractive Industry, Youth Revolt and Global Terrorism in Northern Mozambique - Bonate, Liazzat J. K. (The University of the West Indies, St Augustine, 2018)
The violent insurgency in northern Mozambican province of Cabo Delgado, that started in October 2017 and is still ongoing, caught the government of the country and the public by surprise. Although this insurgency remains largely unexplored and little understood, the only study done so far has suggested that it is being carried out by Muslim youth connected to Islamic radicalism, in particular to the Harakat alShabaab of Somalia and its offshoots in Kenya, Tanzania, and as far as DRC.1 Islam has a long history in Mozambique, since probably the eighth century.2 According to the 2017 National Population Census, Muslims account for about 18% of the total population the country and 58% of the Cabo Delgado inhabitants. However, Mozambique had never had any visible Islamist radical political movement before.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; extractive industries / indústrias extractivas; natural resources - gas / recursos naturais - gás; natural resources / recursos naturais; youth / juventude

Minas a céu aberto de Moçambique - Munguambe, Arcénio Artur; Mandlate, Clarência Matias (Wutivi University, 2018)
Moçambique é um dos países da África com muitos recursos naturais. O grau de conhecime nto geológico até agora atingido, mostra que todos os recursos minerais considerados apresentam perspectivas favoráveis para a sua exploração. A indústria extrativa é o sector que tem grandes empregadores de mão-de-obra e tem um grande impacto rural podendo constituir grandes focos de desenvolvimento e de combate a pobreza nas áreas onde se encontra inserido. Neste caso, o presente trabalho visa identificar os principais recursos naturais e agrupar em metálicos e não metálicos e as respectivas empresas mineradoras.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; extractive industries / indústrias extractivas; natural resources - mining / recursos naturais - mineração; natural resources / recursos naturais

Power, conflict and natural resources: The Mozambican crisis revisited - Macuane, José Jaime; Buur, Lars; Monjane, Celso Marcos (African Affairs, 2018)
This article explores how the present socio-economic crisis in Mozambique is linked to the prospects of natural resource windfalls for the country. Drawing on the political settlement approach, it explores how the distribution of power both within and outside the ruling elite is structured and consequently how the underlying political processes have been shaped by the expectations of natural resource windfalls. The article argues that the present socio-economic crisis in Mozambique is not due to national resource assets in themselves. Instead, the political and economic downturn in Mozambique should be understood as a manifestation of how the political settlement has been organized and rent mobilization controlled by the ruling elite. To understand how the prospect of rents from natural resource sectors have influenced the political settlement, we have argued that one has to look at the dynamics of power both within and outside the ruling elite and the incentives they create for elites to use the control of power and access to economic benefits to achieve narrow and short-term gains rather than inclusive and longer-term goals.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; conflict / conflito; extractive industries / indústrias extractivas; natural resources / recursos naturais; power / poder

Livelihood Interventions and Biodiversity Conservation in Quirimbas National Park - Chevallier, Romy (South African Institute of International Affairs (SAIIA), 2018)
Coastal livelihood interventions can help communities by providing additional incomes, while protecting and maintaining resources and the environment. The identification and promotion of resilient and diversified livelihood opportunities are crucial to enhance communities’ adaptive capacity to respond to the multiple stresses and shocks in a changing coastal environment. Coastal livelihood opportunities are especially important in their support for biodiversity conservation in and around protected areas. Quirimbas National Park (QNP) in Mozambique has some of the greatest marine biodiversity in the region and is one of the country’s largest and most important protected areas. This policy insight considers the most appropriate livelihood-focused interventions for coastal communities in the QNP, taking account of past and current project experiences. In areas where communities and park officials need additional support, it makes recommendations on how to best enhance initiatives.
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; natural resources / recursos naturais

The Project for Supporting the Promotion of Nacala Corridor Development - Final Report - Japan International Cooperation Agency (JICA) (Japan International Cooperation Agency (JICA), 2018)
Final JICA report on Nacala Corridor Development Project, whose objectives include: to clarify organizations for promoting and coordinating the implementation of development strategies for the Nacala Corridor Region in accordance with PEDEC-Nacala and to prepare for the implementation of high priority projects in accordance with PEDEC-Nacala. The study project commenced in April 2012 and the final study report was produced in April 2015.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - Nacala; G - central / centro; G - north / norte; GD - Lichinga; GP - Cabo Delgado; GP - Nampula; GP - Niassa; GP - Tete; GP - Zambézia; L - english / inglês; development partners / parceiros de cooperação; extractive industries / indústrias extractivas; infrastructure / infrastrutura; natural resources / recursos naturais; private sector / setor privado

Extractives and economic diversification in Mozambique: will local content do the trick? (Research Brief 2/2018, 2018)
Research Findings - It is unlikely that the extractives sector can any time soon be used to finance visionary transformation strategies aimed at achieving economic diversification. Due to the country’s fiscal situation and delays in developing the offshore natural gas sector, it seems that extractives will not provide additional revenues for at least another decade, if not longer. If the fiscal crisis results in the further deterioration of the provision of public goods and services, the business environment will become worse for the country’s micro, small and medium-sized enterprises. There is the risk that the gap will widen even further between the skills and entrepreneurial capabilities available in the country, and those required by foreign investment projects and their supply chains. Such a prospect does not match well with the expectations that local content policies can provide the silver bullet for diversifying the economy.
Keywords: FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; L - english / inglês; extractive industries / indústrias extractivas; natural resources / recursos naturais; private sector / setor privado

“Our Lives Mean Nothing” - The Human Cost of Chinese Mining in Nagonha, Mozambique - Amnesty International (Amnesty International, 2018)
This report examines Haiyu’s conduct including what the company did or failed to do in acquiring the right to land for use of mining activity in Nagonha, what it did or failed to do in its operations in Nagonha, and what it did or failed to do in response to the villagers’ demand for compensation and resettlement following the flood. The report looks specifically at the breach of the right to adequate housing and decent living standards ensuing from Haiyu’s destruction of the wetland, and the related destruction of one-fifth of the village by the freak flood. The report also examines the Mozambican Government’s failure to protect, promote and fulfil the right to adequate housing and living standards in the village of Nagonha.
Keywords: *indexed; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; natural resources - mining / recursos naturais - mineração; poverty / pobreza

Economia, recursos naturais, pobreza e política em Moçambique: uma colectânea de textos - Brito, Luís de; Chivulele, Fernanda Massarongo (IESE, 2017)
Neste contexto, o conjunto de textos que compõem a presente colectânea apresenta material útil para a contextualização da situação actual e para o debate dos diferentes problemas que o país enfrenta. As discussões sobre eleições, descentralização, participação, dívida pública, sistema financeiro, crescimento e desenvolvimento económico, dentre outras, que fazem parte da colectânea, informam o debate a nível de praticamente todas as áreas de desafios cruciais que hoje se vivem em Moçambique. Não só são fornecidos pontos relevantes para o debate actual, mas através desta colectânea é possível também fazer um acompanhamento histórico da evolução dos diferentes assuntos e ver como temas actualmente destacados no debate nacional já eram levantados no quadro do trabalho do IESE ao longo dos últimos 9 anos. Por esta via, é igualmente possível questionar até que ponto diferentes análises são usadas e consideradas no debate e na formulação de políticas. A colectânea contém 76 boletins produzidos por investigadores permanentes do IESE e alguns investigadores associados e está subdividida em 5 temáticas. A primeira foca questões ligadas à dívida pública, sistema financeiro e mobilização de recursos. Especificamente, esta parte discute a problemática da dívida pública em Moçambique e suas implicações para a economia, assim como dinâmicas do sector financeiro e mobilização de recursos de forma mais geral. A segunda discute a estrutura e estratégia de crescimento económico e suas implicações, fontes e padrões de investimento privado e ligações económicas existentes na economia. A terceira discute três “P” fundamentais no desenvolvimento económico: pobreza, protecção social e população. A discussão sobre pobreza incide sobre a sua conceptualização e mapeamento e sobre a sua relação com crescimento e governação. Esta discussão continua com a questão da protecção social em Moçambique, tratando aspectos como a pensão universal e as estratégias de protecção social no contexto específico da economia de Moçambique, bem como os desafios demográficos que lhe estão associados. Na quarta parte, os textos tratam da questão dos recursos naturais, seu papel no desenvolvimento, relação de grandes projectos de exploração de terra com o desenvolvimento local e a eficácia dos mecanismos concebidos para reforçar a transparência na exploração de recursos naturais. A última parte discute a questão da descentralização, mecanismos de participação da sociedade civil e questões relativas aos processos eleitorais em Moçambique.
Keywords: *snowball; G - Mozambique / Moçambique; L - portuguese / português; economic development / desenvolvimento económico; natural resources / recursos naturais; poverty / pobreza

Elite capture and the development of natural resource linkages in Mozambique - Buur, Lars; Monjane, Celso Marcos (Fairness and Justice in Natural Resource Politics, 2017)
This chapter explores these broader processes from the perspective of linkage creation in Mozambique related to mega-projects in natural resource extraction and development from a political economy perspective. From a resource fairness perspective, linkage creation is essential as it allows for a more fair distribution of opportunities for local firms to gain from large-scale natural resource investments and for learning and spillover effects to other parts of the economy. In a longer term perspective, it is a potential key source of economic transformation towards higher value added activities and more and better local employment, therefore reducing dependence on resources.
Keywords: FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; natural resources / recursos naturais

Overblown expectations of the mining sector - Economist Intelligence (Economist Intelligence, 2016)
The government of Mozambique remains confident that its mining boom is set to accelerate in the coming years, despite weak sentiment in the global mining industry. Rising coal production and an eventual rebound in global prices will spur some growth in Mozambique's mining sector in 2016‑20 but we expect that, weighed down by infrastructure deficits and non-competitive policies, it will remain a relatively small contributor to GDP growth. Mozambique has untapped coal reserves estimated to be in excess of 20bn tonnes, as well as commercial quantities of aluminium, gold, titanium, graphite and gemstones. Plus, it benefits from a long coastline and geographic proximity to mineral-hungry markets in Asia. At the peak of the commodity super-cycle, investor interest in Mozambican mining soared; the contribution of the mining sector to GDP increased from 1.6% in 2009 to 3.2% in 2013, while government earnings from the sector swelled from US$40m in 2009 to over US$1bn in 2014.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; extractive industries / indústrias extractivas; natural resources - mining / recursos naturais - mineração; natural resources / recursos naturais

Estrutura Geológica de Moçambique - Nogar Boca (2016)
Tema: Estrutura Geológica de Moçambique A estrutura geológica de Moçambique é resultado da interacção de vários processos, sobretudo os endógenos (internos) e exógenos (externos), que se fizeram sentir e ainda sentem-se na actual região da África Austral, onde Moçambique faz parte. Do ponto de vista geológico, Moçambique apresenta duas grandes unidades geológicas: Pré-câmbrico Fanerozóico
Keywords: G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; natural resources / recursos naturais

Estratégia da Suécia para a cooperação para o desenvolvimento com Moçambique, 2015-2020 - Ministry for Foreign Affairs - Sweden (Ministry for Foreign Affairs - Sweden, 2015)
Within the framework of this strategy, Swedish development cooperation with Mozambique aims to make use of the increased interest and potential to utilise the country's natural resources in a socially, economically and environmentally sustainable way. It also aims to improve opportunities for people living in poverty to contribute to and benefit from economic and democratic development. The strategy is valid for the period 2015–2020 and comprises a total of SEK 4.1 billion.
Keywords: G - Mozambique / Moçambique; L - portuguese / português; economic development / desenvolvimento económico; natural resources / recursos naturais

Strategy for Sweden’s development cooperation with Mozambique, 2015–2020 - Ministry for Foreign Affairs - Sweden (Ministry for Foreign Affairs - Sweden, 2015)
Within the framework of this strategy, Swedish development cooperation with Mozambique aims to make use of the increased interest and potential to utilise the country's natural resources in a socially, economically and environmentally sustainable way. It also aims to improve opportunities for people living in poverty to contribute to and benefit from economic and democratic development. The strategy is valid for the period 2015–2020 and comprises a total of SEK 4.1 billion.
Keywords: G - Mozambique / Moçambique; L - english / inglês; economic development / desenvolvimento económico; natural resources / recursos naturais

Gás para desenvolvimento ou apenas dinheiro? - Hanlon, Joseph; Nuvunga, Adriano (Centro de Integridade Pública (Public Integrity Centre), 2015)
O gás de Moçambique pode ser usado para promover industrialização e desenvolvimento rural desde que, a partir de agora, sejam feitas as opções correctas. As actuais prioridades vão para os megaprojectos baseados na exportação, que prometem altos rendimentos mas que, tal como os megaprojectos anteriores, fazem pouco pela criação de empregos ou pela redução da pobreza. Os megaprojectos custando dezenas de bilhões de dólares são essenciais, mas o Conselho de Ministros pode orientar as negociações de maneira a darem a prioridade mais alta à utilização do gás para criar uma indústria nacional e empregos, mesmo que reduza as receitas a curto prazo
Keywords: *indexed; *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; extractive industries / indústrias extractivas; natural resources - gas / recursos naturais - gás; natural resources / recursos naturais; rural development / desenvolvimento rural

Gas for development or just for money? - Hanlon, Joseph; Nuvunga, Adriano (Centro de Integridade Pública (Public Integrity Centre), 2015)
Mozambique’s gas can be used to promote industrialisation and rural development, but only if key choices are made now. Current priorities are for export based mega-projects promising high revenues, but like past mega-projects doing little to create jobs or reduce poverty. Mega-projects costing tens of billions of dollars are essential, but the Council of Ministers can instruct that negotiations give a higher priority to using the gas to create a domestic industry and jobs, even if it reduces short term income.
Keywords: *indexed; *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; extractive industries / indústrias extractivas; natural resources - gas / recursos naturais - gás; natural resources / recursos naturais; rural development / desenvolvimento rural

Natural Gas and Socio-Economic Transformation in Mozambique: Some Preliminary Evidence - Uetela, Pedro; Obeng-Odoom, Franklin (The Journal of Energy and Development, 2015)
The aim of this article is to extend the state of analysis on the impacts of gas development in Mozambique by evaluating the relationship between the gas sector, the Mozambican economy, and social change. As the resource curse framework is only limited to economic growth, this work utilizes two alternative frameworks—the Staples approach and the Linkages approach—that are melded into an institutional analysis, looking simultaneously at “benefits, costs, and uncertainties” or “blessings, uncertainties, and curses,” and used to conceptualize progress more widely to include not only growth, but other externalities and broader social change as applied to the case of Mozambique. In so doing, the evidence suggests that the natural gas industry in Mozambique has contributed to both the expansion in economic growth and social change. However, the positive experience with social change arises from direct intervention and not necessarily the result of the related economic growth. Indeed, in the process of economic growth, the production and export of natural gas in Mozambique have raised the possibility of major socio-economic and ecological dangers. Contrary to the theoretical criticism of spending windfall revenues on social services as wasteful, we argue that only strategic social and ecological expenditures of gas revenues can provide and increase the chances of the gas industry becoming transformational economically, socially, and ecologically. The article is organized as follows; the next section deals with conceptualizing the paper and describing the sources of data. This is followed by sections that present the results, a discussion of those results, and conclusions and policy implications from the study.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; economic development / desenvolvimento económico; extractive industries / indústrias extractivas; natural resources - gas / recursos naturais - gás; natural resources / recursos naturais; ⛔ No DOI found

Artisanal gold mining and rural development policies in Mozambique: Perspectives for the future - Dondeyne, Stefaan; Ndunguru, Eduardo (Futures, 2014)
Despite Mozambique's great natural resource wealth and strong economic growth, rural poverty remains high countrywide. The challenge is thus finding ways to turn this wealth into development opportunities. For many rural people in central Mozambique, artisanal gold mining is the most direct source of income and this is most likely to remain so. Drawing on our personal experiences, we reflect on the future of artisanal gold mining in Mozambique. The government's strategy consists of promoting improved technologies and encouraging artisanal miners to establish themselves as businesses by creating miners associations. This has proved successful where the ore allows for sufficiently long exploitation, in practice, where reef gold occurs. The same cannot be said, however, of colluvial or alluvial deposits, where placer gold is mined. Given the variable nature of these deposits, accompanying mining activities are relatively short-lived at such sites. In these cases, local authorities and community representatives must play an expanded role in enforcing good mining practices. Doing so would be in line with the country's current decentralisation and democratisation policies in relation to rural development.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - central / centro; GP - Sofala; L - english / inglês; natural resources - mining / recursos naturais - mineração; natural resources / recursos naturais; rural development / desenvolvimento rural

Brief presentation of the geological resources of Mozambique - Vasconcelos, Lopo (2014)
This paper aims at giving a general overview on the geology of Mozambique, and its mineral and geological resources associated to the different geological units. The geology of Mozambique covers almost all periods of the Earth’s history. Tectonically speaking, Precambrian is found in three Gondwana blocks – E, W and S -, each one of them with its geostructural characteristics, and separated from each other by great structural features. For Phanerozoic, reference is made to the Karoo Supergroup (Upper Carboniferous to Early Jurassic), and to the East- Africa Rift System (Jurassic to the present), with origin linked to the Gondwana fragmentation and the opening of the Mozambique Channel, where the great sedimentary basins of Rovuma (N) and Mozambique (center-S) can be distinguished, both world-wide known for the discoveries of hydrocarbons. A general presentation of the geological resources and their location. © 2014, LNEG – Laboratório Nacional de Geologia e Energia IP.
Keywords: G - Mozambique / Moçambique; L - english / inglês; natural resources / recursos naturais

Indústria extractiva e desenvolvimento local: O papel da responsabilidade social empresarial - Langa, Epifânia; Massingue, Nelsa (Desafios para Moçambique, 2014)
A entrada de grandes investimentos de capitais estrangeiros na área de recursos minerais e energia, nos últimos anos, tem levantado várias questões sobre o papel dos mega ‑projectos no desenvolvimento económico e social em Moçambique, gerando um debate sem consenso. Uma das temáticas do debate é a responsabilidade social empresarial (RSE). Acções de RSE como a construção de infra ‑estruturas sociais para a educação e a saúde, a geração de emprego, entre outras são muitas vezes referenciadas em muitos discursos, principalmente políticos e de empresas, como aspectos positivos que complementam as acções do governo, devendo por isso ser promovidas e valorizadas.1 Entretanto, estes discursos muitas vezes negligenciam componentes não menos importantes como a intenção das empresas ao desen‑ volver iniciativas sociais, o risco das comunidades se tornarem dependentes destes mega ‑projectos e a possibilidade de fragilização do papel do Estado (Schroeder & Schroeder, 2004).
Keywords: G - Mozambique / Moçambique; L - portuguese / português; extractive industries / indústrias extractivas; natural resources / recursos naturais; private sector - CSR (corporate social responsibility) / setor privado - RSC (responsabilidade social corporativa); private sector / setor privado

A Rede de Negocios da Frelimo no Norte - , Erik (Verdade - A verdade a cada palavra, 2013)
O investimento em energias e infra-estruturas pode transformar o negligenciado norte e afectar a sucessão presidencial. Andarko e outras companhias petrolíferas prevêem que o gás descoberto em Cabo Delgado pode duplicar o produto interno bruto anual. Por enquanto acredita-se que as vastas reservas de carvão se encontram na província do Niassa. O centro de gravidade de oportunidades económicas de Moçambique parecem se transladar para o norte. O governo está a atrair investidores estrangeiros para ajudarem na transformação desses recursos naturais em rendimentos públicos para o que era até agora um dos países mais pobres do mundo.
Keywords: #Reporting & Media / Reportagem & Mídia; G - north / norte; GP - Cabo Delgado; infrastructure - energy / infrastrutura - energia; natural resources / recursos naturais

APRM Country Review Report Mozambique - República de Moçambique (República de Moçambique, 2009)
The major cross-cutting issues which featured prominently in all the thematic areas are highlighted below. A comprehensive approach is needed to address these issues as they have wider ramification for the various dimensions of governance in Mozambique. The following are the major thirteen crosscutting issues emerging from this report: Poverty and Inequality; Party/government/business dichotomy; HIV/AIDs; Land Ownership; High levels of illiteracy; High aid dependency; Information flow and paucity of data; Inclusivity; Crime, safety and Security; Domestic violence; Capacity constraints and implementation challenge; Elections; and, Corruption. CONCLUSION: The remarkable recovery that Mozambique has made since the end of the civil war in 1992 should make the people proud of their accomplishments. Over the last two decades, Mozambicans has made considerable progress in rebuilding its political, economic and social institutions, with noticeable progress. There is no doubt that Mozambicans can build on the successes highlighted in this report, while addressing the challenges in a vigorous manner, in order for the country to rapidly move forward. With its abundant natural resources, Mozambicans can exploit these resources for the benefit of the majority of its people. But this will be difficult to achieve without pragmatic and innovative solutions to the challenges arising from both the thematic and cross-cutting issues identified by this report.
Keywords: *non-public; G - Mozambique / Moçambique; L - english / inglês; conflict - civil war / conflito - guerra civil; governance / governação; health / saúde; natural resources / recursos naturais; poverty / pobreza

Institutional Change and Community Based Natural Resource Management in Northern Mozambique - Anstey, Simon (University of Zimbabwe, 2009)
The objective of this study is to examine how the extensive institutional change of reforms to policy and legislation in Mozambique over the past decade has affected evolutions at the local level in the governance of natural resources. The particular focus of the research is an analysis of a community based natural resource management (CBNRM) initiative in North Sanga District of Niassa Province and a longitudinal study of its development between 1999 and 2007 based on my involvement as both field practioner and researcher. The research reveals institutional change in the governance of natural resources by communities in North Sanga as non-linear, non-equilibrium and scale interactive; as well as the agency in change being contingent on specific contexts (historical, social and environmental) and responsive to the beliefs of the actors involved. The importance of ‘crisis’ in promoting new cycles of adaptation for local governance is emphasised as is the significance of gaining formal ownership of the land by the community in acting as a key promoter of their agency in institutional and governance change.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - english / inglês; governance / governação; land governance / gestão de terra; natural resources / recursos naturais

Mineral Resources Potential in Mozambique - Lehto, Tapio; Gonçalves, Reinaldo (Geological Survey of Finland, 2008)
The metallic mineral, industrial mineral and construction material resources in Mozambique have been mapped as part of the Mineral Resources Management Capacity Building Project, financed by a grant provided by the Nordic Development Fund. A database covering the location and characteristics of more than 600 mineral indications, showings and deposits within the geographical contract area assigned to the GTK Consortium was created. A total of 140 mineral occurrences were selected for field surveys and assessments that were mainly carried out during May-November 2003, 2004 and 2005. All available data in the report archives of the client, the National Directorate of Geology (DNG), was collected and transferred to the mineral occurrence database, which was then updated with information from field surveys and with new data published by exploration and mining companies on the Internet. New mineral resources maps at the scales 1:50 000 (part of contract area), 1:250 000 and 1:1 million were prepared with the corresponding symbols for various commodities plotted. Favourability maps showing zones with high potential for selected commodities were compiled at the 1:250 000 scale. The mineral resources in Mozambique were described in the four map explanation volumes and summarized in the final reports for the projects Geological Mapping LOT 2 and Geological Mapping LOT 3. As a consequence of increased geological knowledge, facilitated by the activities of the GTK Consortium, investments in Mozambique’s mineral potential by leading international and regional mining companies is already increasing. Currently, global mining houses are investing in exploration for energy minerals (hydrocarbons, coal and uranium), for titanium and zirconium in heavy mineral sands, for gold and gemstones, for the agricultural minerals lime and phosphate and for tantalum, fluorite and other industrial minerals.
Keywords: G - Mozambique / Moçambique; L - english / inglês; natural resources - mining / recursos naturais - mineração; natural resources / recursos naturais; ⛔ No DOI found

Exploring Natural Resources in Mozambique: Will it be a Blessing or a Curse? - Bacuane, Aurélio; Mulder, Peter (Instituto de Estudos Sociais e Económicos (IESE), 2007)
Mozambique has considerable quantity of natural resources, of which the major part is yet to be explored. The Government of Mozambique is determined to extract and export its natural resource potential as soon as possible, supposing that this will positively contribute to economic growth and poverty reduction. However, any resources rich countries are among the poorest nations in the world, in spite of decennia-long exploration of their natural wealth. This so colled 'paradox of plenty' or 'resource curse' raises the question whether the foreseen exploration of natural resources in Mozambique will pose a serious threat rather than a blessing to its economic development. In this paper we first estimate the potential resource wealth of Mozambique in comparison to other countries. Next, we briefly review the rowing body of literature on the existence and determinants of a natural resource curse. Then we evaluate the risk of a resource curse to occur in Mozambique in the (near) future. Finally, we try to come up with suggestions to avert a Mozambican resource curse.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; M - political economy analysis (PEA) / análise de economia política (AEP); extractive industries / indústrias extractivas; institutions / instituições; natural resources - gas / recursos naturais - gás; natural resources / recursos naturais; transparency / transparência

The resource curse: which institutions matter? - Kolstad, Ivar; Chr. Michelsens institutt (Chr. Michelsen Institute, 2007)
Two types of models are dominant in the current resource curse literature. One type of model studies the selection of entrepreneurs into rent-seeking versus productive activities. The other type analyses the use of patronage by politicians seeking re-election. The policy implications of the two models are quite different. The first model suggests that institutions governing the private sector ought to be improved. The second model suggests that institutions governing the public sector should be emphasized. This article empirically tests the impact of the private versus public sector institutions on the resource curse, using cross-country data from Sachs and Warner (1997a) and Polity IV. The main result is that only improved private sector institutions ameliorate the resource curse.
Keywords: L - english / inglês; institutions / instituições; natural resources / recursos naturais